Dominasi Hard Skill atas Soft Skill dalam Menentukan Kesiapan Kerja Fresh Graduate - Linda Daniati Melinda (ATRABIS Jurnal Administrasi Bisnis (e-Journal), 2026)
This study examines the effect of soft skills and hard skills on the work readiness of fresh graduates from Politeknik X. A quantitative causal-associative survey design with a cross-sectional approach was employed, involving a census (total sampling) of the entire population of 61 fresh graduates. Data were collected through a five-point Likert-scale questionnaire and analyzed using corrected item-total correlation for validity, Cronbach's Alpha for reliability, classical assumption tests, and multiple linear regression. After eliminating invalid items, the instrument demonstrated adequate validity and reliability (α ≥ 0.70) for all variables, and all classical assumptions were satisfied. The regression results showed that hard skills had a positive and significant effect on work readiness (B = 0.540; p < 0.001), whereas soft skills showed no significant partial effect (B = -0.018; p = 0.802). Simultaneously, soft skills and hard skills significantly influenced work readiness (F = 16.677; p < 0.001), explaining 36.5% of its variance (R² = 0.365). These findings indicate that, within the vocational-technical context of Politeknik X, hard skills serve as the dominant predictor of work readiness, while the role of soft skills appears to be more contextual and may be constrained by self-report measurement limitations. The study offers empirical insight for evaluating vocational curricula and soft-skill assessment strategies in technical higher education institutions.